The Taste of Silence : How I Came to Be at Home with Myself - Vandekerckhove, Bieke (Book collections on Project MUSE., 2015)
At nineteen, Bieke Vandekerckhove fell ill. The diagnosis was devastating: the fatal motor neuron disease ALS. Life expectancy: two to five years. So what did she do with the paltry bit of life that was left? By force of circumstance, she was led to Saint Lioba Convent in Egmond-Binnen. There she learned Benedictine spirituality and to pray the psalms, which influenced her life for good. Three years later, she learned that her illness had gone into remission but that it could flare up again at any time. She has been living with ALS for twenty years now. She is married and has two assistants to help her as necessary. Ten years ago, she found the silence of Zen. This encounter also proved decisive. The Taste of Silence reflects what she experienced, saw, and tasted in the stillness of life: 'Benedictine spirituality and Zen Buddhism became the two lungs through which I breathe.'